Analisis Lingkungan Pengendalian dalam Pelaksanaan SPIP di Inspektorat Kabulaten Nagekeo - Andy Andreas Corsini Mosa Leke; R. Ira Irawati; Candradewini Candradewini (Owner : Riset dan Jurnal Akuntansi, 2022)
ABSTRACTThe control environment is a crucial object in the whole control activities carried out, thus without an effective control environment, internal control will not work effectively. The Inspectorate of Nagekeo Regency as an institution that assists the Regent in supervising the implementation of regional Government by conducting inspections, studies, evaluations, and other supervisory activities at other government institutions within the Scope of Government of Nagekeo Regency, have to have an adequate control environment in support of effective internal control activities. The used object of research in this study is the control environment built by the Regency Inspectorate Employees who taken by purposive sampling technique. This measure is used as a comparison in the control environment assessment category. This study uses a quantitative-descriptive technique with a field research approach at the Inspectorate of Nagekeo Regency. The variables of this study are the control environment sub-elements with eight variables which include the enforcement of integrity and ethical values, commitment to competence; Conducive leadership; Establishment of organizational structure as needed; Appropriate delegation of authority and responsibility; Formulation and implementation of sound human resource development policies; The realization of the role of an effective government internal control apparatus; and good working relationship with relevant Government Agencies. In general, the eight variables of the Nagekeo Inspectorate get a score of 2.25 with quite-adequate predicate. However, two of them that still get the inadequate predicate, including the Enforcement of Integrity and Ethics; Formulation and implementation of human resource development policies, need to get attention.